2006
DOI: 10.1086/507068
|View full text |Cite
|
Sign up to set email alerts
|

Can We Trust the Dust? Evidence of Dust Segregation in Molecular Clouds

Abstract: Maps of estimated dust column density in molecular clouds are usually assumed to reliably trace the total gas column density structure. In this work we present results showing a clear discrepancy between the dust and the gas distribution in the Taurus molecular cloud complex. We compute the power spectrum of a 2MASS extinction map of the Taurus region and find that it is much shallower than the power spectrum of a 13 CO map of the same region that was previously analyzed. This discrepancy could be explained as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 39 publications
4
43
1
Order By: Relevance
“…The changes in dustgrain properties within dense clouds and small scale variations in the gas-to-dust ratio remain possible sources of uncertainty when any dust tracers are used to infer the distribution of total cloud mass (e.g. Padoan et al 2006b). On the other hand, by providing high resolution images of the dust distribution the near-infrared scattering also provides a useful tool for the study of these questions.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in dustgrain properties within dense clouds and small scale variations in the gas-to-dust ratio remain possible sources of uncertainty when any dust tracers are used to infer the distribution of total cloud mass (e.g. Padoan et al 2006b). On the other hand, by providing high resolution images of the dust distribution the near-infrared scattering also provides a useful tool for the study of these questions.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several studies have suggested that dust grains in GMCs or neutral galactic disks should exhibit similar fluctu-E-mail:hlee2@mit.edu ations (Padoan et al 2006;Hopkins 2014b;Hopkins & Conroy 2015) -in terms of the aerodynamic drag equations, a grain of diameter ∼ 0.1−1 µm in a typical GMC is analogous to a meter-sized boulder in a protoplanetary disk. And observations have identified small-scale (∼ 0.01−1 pc) fluctuations in the local dust-to-gas ratio of large grains in a number of nearby molecular clouds (Thoraval et al 1997(Thoraval et al , 1999Abergel et al 2002;Flagey et al 2009;Boogert et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The same phenomenon of "preferential concentration" is wellknown in both laboratory experiments and simulations of terrestrial turbulence (Squires & Eaton 1991;Rouson & Eaton 2001;Monchaux et al 2010Monchaux et al , 2012Pan et al 2011). Because the dynamics are scale-free, the same phenomena governing pebbles and boulders in a protoplanetary disk should apply tosubmicron size dust in a giant molecular cloud (Padoan et al 2006;Yoshimoto & Goto 2007;Bec et al 2009;Olla 2010;Hopkins 2016a). And indeed, dust-to-gas ratio fluctuations on scales of ∼0.003-10 pc have been measured in many nearby molecular clouds and insome galaxy nuclei (e.g., Orion, Taurus, and many more;see Thoraval et al 1997Thoraval et al , 1999Abergel et al 2002;MivilleDeschênes et al 2002;Padoan et al 2006;Flagey et al 2009;Pineda et al 2010;Nyland et al 2013); thedependence on dust grain size is in good agreement with the predictions of turbulent concentration (Padoan et al 2006;Hopkins 2014).…”
mentioning
confidence: 88%